This action might not be possible to undo. Are you sure you want to continue?
7 Let R
2
be the resistance seen looking into the collector of Q
2
.
R
out
= r
o1
+ (1 +g
m1
r
o1
) (r
π1
R
2
)
Note that this expressoin is maximized as R
2
→∞. This gives us
R
out,max
= r
o1
+ (1 +g
m1
r
o1
) r
π1
9.9
R
out
≈
1
I
C1
V
A
V
T
βV
A
V
T
V
A
+βV
T
(Eq. 9.9)
=
1
I
C1
V
A
V
T
βV
T
=
βV
A
I
C1
= βr
o
This resembles Eq. (9.12) because the assumption that
V
A
≫βV
T
can be equivalently expressed as
V
A
I
C
≫β
V
T
I
C
r
o
≫r
π
This is the same assumption used in arriving at Eq. (9.12).
9.12
I
D
= 0.5 mA
R
out
= r
o1
+ (1 +g
m1
r
o1
) r
o2
=
1
λI
D
+
_
1 +
_
2
W
L
µ
n
C
ox
I
D
1
λI
D
_
1
λI
D
≥ 50 kΩ
λ ≤ 0.558 V
−1
9.15 (a)
V
D1
= V
DD
−I
D
R
D
= 1.3 V > V
G1
−V
TH
= V
b1
−V
TH
V
b1
< 1.7 V
(b)
V
b1
= 1.7 V
V
GS1
= V
b1
−V
X
= V
TH
+
¸
2I
D
_
W
L
_
1
µ
n
C
ox
= 0.824 V
V
X
= 0.876 V
9.16 (a) Looking down from the source of M
1
, we see an equivalent resistance of
1
gm2
r
o2
. Thus, we have
R
out
= g
m1
r
o1
_
1
g
m2
r
o2
_
(b)
R
out
= g
m1
r
o1
r
o2
(c) Putting two transistors in parallel, their transconductances will add and their output resistances
will be in parallel (i.e., we can treat M
1
and M
3
as a single transistor with g
m
= g
m1
+g
m3
and
r
o
= r
o1
r
o3
). This can be seen from the smallsignal model.
R
out
= (g
m1
+g
m3
) (r
o1
r
o3
) r
o2
(d) Let’s draw the smallsignal model and apply a test source to ﬁnd R
out
.
+
v
gs1
−
g
m1
v
gs1
r
o1
+
v
gs2
−
−
v
t
+
i
t
g
m2
v
gs2
r
o2
i
t
= g
m2
v
gs2
−
v
gs1
r
o2
= g
m1
v
gs1
+
v
gs2
+v
gs1
r
o1
v
gs1
= g
m2
r
o2
v
t
−i
t
r
o2
i
t
= g
m1
(g
m2
r
o2
v
t
−i
t
r
o2
) +
v
t
+g
m2
r
o2
v
t
−i
t
r
o2
r
o1
i
t
_
1 +g
m1
r
o2
+
r
o2
r
o1
_
= v
t
_
g
m1
g
m2
r
o2
+
1 +g
m2
r
o2
r
o1
_
i
t
(g
m1
r
o1
r
o2
) = v
t
(g
m1
g
m2
r
o1
r
o2
)
R
out
=
v
t
i
t
=
1
g
m2
9.17
I
D
= 0.5 mA
R
out
= r
o1
+ (1 +g
m1
r
o1
) r
o2
=
1
λI
D
+
_
1 +
¸
2
_
W
L
_
1
µ
p
C
ox
I
D
1
λI
D
_
1
λI
D
= 40 kΩ
_
W
L
_
1
=
_
W
L
_
2
= 8
9.20 (a)
G
m
= g
m1
R
out
=
1
g
m2
r
o1
A
v
= −g
m1
_
1
g
m2
r
o1
_
(b)
G
m
= −g
m2
R
out
=
1
g
m2
r
o2
r
o1
A
v
= g
m2
_
1
g
m2
r
o2
r
o1
_
(c) Let’s draw the smallsignal model to ﬁnd G
m
.
v
in
r
π1
+
v
π1
−
R
E
g
m1
v
π1
r
o1
i
out
i
out
= −
v
π1
r
π1
+
v
in
−v
π1
R
E
v
π1
= v
in
+ (i
out
− g
m1
v
π1
) r
o1
v
π1
(1 +g
m1
r
o1
) = v
in
+i
out
r
o1
v
π1
=
v
in
+i
out
r
o1
1 +g
m1
r
o1
i
out
= −
v
in
+i
out
r
o1
r
π1
(1 +g
m1
r
o1
)
+
v
in
R
E
−
v
in
+i
out
r
o1
R
E
(1 +g
m1
r
o1
)
i
out
_
1 +
r
o1
r
π1
(1 +g
m1
r
o1
)
+
r
o1
R
E
(1 + g
m1
r
o1
)
_
= v
in
_
1
R
E
−
1
r
π1
(1 +g
m1
r
o1
)
−
1
R
E
(1 +g
m1
r
o1
)
_
i
out
r
π1
R
E
(1 +g
m1
r
o1
) +r
o1
R
E
+r
o1
r
π1
r
π1
R
E
(1 +g
m1
r
o1
)
= v
in
r
π1
(1 +g
m1
r
o1
) −R
E
−r
π1
r
π1
R
E
(1 + g
m1
r
o1
)
i
out
[r
π1
R
E
(1 +g
m1
r
o1
) +r
o1
R
E
+r
o1
r
π1
] = v
in
[r
π1
(1 +g
m1
r
o1
) −R
E
−r
π1
]
G
m
=
i
out
v
in
=
r
π1
(1 +g
m1
r
o1
) −R
E
−r
π1
r
π1
R
E
(1 +g
m1
r
o1
) + r
o1
R
E
+r
o1
r
π1
≈
g
m1
1 +g
m1
R
E
(if r
π1
, r
o1
are large)
R
out
= r
o2
[r
o1
+ (1 +g
m1
r
o1
) (r
π1
R
E
)]
A
v
= −
r
π1
R
E
(1 +g
m1
r
o1
) −R
E
−r
π1
r
π1
R
E
(1 +g
m1
r
o1
) +r
o1
R
E
+r
o1
r
π1
{r
o2
[r
o1
+ (1 +g
m1
r
o1
) (r
π1
R
E
)]}
(d)
G
m
= g
m2
R
out
= r
o2
[r
o1
+ (1 +g
m1
r
o1
) (r
π1
R
E
)]
A
v
= −g
m2
{r
o2
[r
o1
+ (1 +g
m1
r
o1
) (r
π1
R
E
)]}
(e) Let’s draw the smallsignal model to ﬁnd G
m
.
+
v
gs1
−
R
S
v
in
g
m1
v
gs1
r
o1
i
out
Since the gate and drain are both at AC ground, the dependent current source looks like a resistor
with value 1/g
m1
. Thus, we have:
G
m
=
i
out
v
in
= −
1
R
S
+
1
gm1
r
o1
= −
1
R
S
+
ro1
1+gm1ro1
= −
1 +g
m1
r
o1
r
o1
+R
S
+g
m1
r
o1
R
S
≈ −
g
m1
1 +g
m1
R
S
(if r
o1
is large)
R
out
= [r
o2
+ (1 +g
m2
r
o2
) R
E
] [r
o1
+ (1 +g
m1
r
o1
) R
S
]
A
v
=
1 +g
m1
r
o1
r
o1
+R
S
+g
m1
r
o1
R
S
{[r
o2
+ (1 +g
m2
r
o2
) R
E
] [r
o1
+ (1 + g
m1
r
o1
) R
S
]}
(f) We can use the result from part (c) to ﬁnd G
m
here. If we simply let r
π
→∞ (and obviously we
replace the subscripts as appropriate) in the expression for G
m
from part (c), we’ll get the result
we need here.
G
m
= lim
rπ2→∞
r
π2
R
E
(2 +g
m2
r
o2
) −R
E
−r
π2
r
π2
R
E
(2 +g
m2
r
o2
) +r
o2
R
E
+r
o2
r
π2
=
g
m2
r
o2
r
o2
+R
E
+g
m2
r
o2
R
E
≈
g
m2
1 +g
m2
R
E
(if r
o2
is large)
R
out
= [r
o2
+ (1 +g
m2
r
o2
) R
E
] [r
o1
+ (1 +g
m1
r
o1
) R
S
]
A
v
= −
g
m2
r
o2
r
o2
+R
E
+g
m2
r
o2
R
E
{[r
o2
+ (1 +g
m2
r
o2
) R
E
] [r
o1
+ (1 +g
m1
r
o1
) R
S
]}
(g) Once again, we can use the result from part (c) to ﬁnd G
m
here (replacing subscripts as appro
priate).
G
m
=
r
π2
R
E
(1 +g
m2
r
o2
) −R
E
−r
π2
r
π2
R
E
(1 +g
m2
r
o2
) +r
o2
R
E
+r
o2
r
π2
≈
g
m2
1 +g
m2
R
E
(if r
π2
, r
o2
are large)
R
out
= R
C
[r
o2
+ (1 +g
m2
r
o2
) (r
π2
R
E
)]
A
v
= −
r
π2
R
E
(1 +g
m2
r
o2
) −R
E
−r
π2
r
π2
R
E
(1 +g
m2
r
o2
) +r
o2
R
E
+r
o2
r
π2
{R
C
[r
o2
+ (1 +g
m2
r
o2
) (r
π2
R
E
)]}
9.22
A
v
= −g
m1
[r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)]
I
C1
≈ I
C2
= I
1
V
A1
= V
A2
= V
A
A
v
≈ −
I
1
V
T
_
V
A
I
1
+
_
1 +
V
A
V
T
__
βV
T
I
1
V
A
I
1
__
= −500
V
A1
= V
A2
= 0.618 V
−1
9.23 (a) Although the output resistance of this stage is the same as that of a cascode, the transconductance
of this stage is lower than that of a cascode stage. A cascode has G
m
= g
m
, where as this stage
has G
m
=
gm2
1+gm2ro1
.
(b)
G
m
=
g
m2
1 +g
m2
r
o1
R
out
= r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)
A
v
= −G
m
R
out
= −
g
m2
1 +g
m2
r
o1
[r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)]
9.24
G
m
= −g
m1
R
out
= r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)
A
v
= g
m1
[r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)]
9.25 (a)
G
m
= g
m2
R
P
r
π1
1
gm1
+R
P
r
π1
R
out
= r
o1
+ (1 +g
m1
r
o1
) (r
π1
r
o2
R
P
)
A
v
= −g
m2
R
P
r
π1
1
gm1
+R
P
r
π1
[r
o1
+ (1 +g
m1
r
o1
) (r
π1
r
o2
R
P
)]
(b)
G
m
= g
m2
R
out
= r
o1
R
P
+ [1 +g
m1
(r
o1
R
P
)] (r
π1
r
o2
)
A
v
= −g
m2
{r
o1
R
P
+ [1 +g
m1
(r
o1
R
P
)] (r
π1
r
o2
)}
(c)
G
m
=
g
m2
1 +g
m2
R
E
R
out
= r
o1
+ (1 +g
m1
r
o1
) [r
π1
(r
o2
+ (1 +g
m2
r
o2
) (r
π2
R
E
))]
A
v
= −
g
m2
1 + g
m2
R
E
{r
o1
+ (1 +g
m1
r
o1
) [r
π1
(r
o2
+ (1 +g
m2
r
o2
) (r
π2
R
E
))]}
(d)
G
m
= g
m2
R
out
= r
o1
+ (1 +g
m1
r
o1
) (r
π1
r
o2
r
o3
)
A
v
= −g
m2
[r
o1
+ (1 +g
m1
r
o1
) (r
π1
r
o2
r
o3
)]
9.26
A
v
= −g
m1
{[r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)] [r
o3
+ (1 +g
m3
r
o3
) (r
π3
r
o4
)]}
= −
I
C
V
T
__
V
A,N
I
C
+
_
1 +
V
A,N
V
T
__
β
N
V
T
I
C
V
A,N
I
C
__
_
V
A,P
I
C
+
_
1 +
V
A,P
V
T
__
β
P
V
T
I
C
V
A,P
I
C
___
= −
I
C
V
T
_
VA,N
IC
+
_
1 +
VA,N
VT
__
βNVT
IC
VA,N
IC
__ _
VA,P
IC
+
_
1 +
VA,P
VT
__
βPVT
IC
VA,P
IC
__
_
VA,N
IC
+
_
1 +
VA,N
VT
__
βNVT
IC
VA,N
IC
__
+
_
VA,P
IC
+
_
1 +
VA,P
VT
__
βPVT
IC
VA,P
IC
__
= −
I
C
V
T
_
VA,N
IC
+
_
1 +
VA,N
VT
_
βNVT VA,N
I
2
C
“
β
N
V
T
I
C
+
V
A,N
I
C
”
__
VA,P
IC
+
_
1 +
VA,P
VT
_
βP VT VA,P
I
2
C
“
β
P
V
T
I
C
+
V
A,P
I
C
”
_
_
VA,N
IC
+
_
1 +
VA,N
VT
_
βNVT VA,N
I
2
C
“
β
N
V
T
I
C
+
V
A,N
I
C
”
_
+
_
VA,P
IC
+
_
1 +
VA,P
VT
_
βPVT VA,P
I
2
C
“
β
P
V
T
I
C
+
V
A,P
I
C
”
_
= −
I
C
V
T
1
I
2
C
_
V
A,N
+
_
1 +
VA,N
VT
_
βNVT VA,N
βNVT +VA,N
_ _
V
A,P
+
_
1 +
VA,P
VT
_
βPVT VA,P
βPVT +VA,P
_
1
IC
_
V
A,N
+
_
1 +
VA,N
VT
_
βNVT VA,N
βNVT +VA,N
_
+
1
IC
_
V
A,P
+
_
1 +
VA,P
VT
_
βPVT VA,P
βPVT +VA,P
_
= −
1
V
T
_
V
A,N
+
_
1 +
VA,N
VT
_
βNVT VA,N
βNVT +VA,N
_ _
V
A,P
+
_
1 +
VA,P
VT
_
βPVT VA,P
βPVT +VA,P
_
_
V
A,N
+
_
1 +
VA,N
VT
_
βNVT VA,N
βNVT +VA,N
_
+
_
V
A,P
+
_
1 +
VA,P
VT
_
βP VT VA,P
βPVT +VA,P
_
The result does not depend on the bias current.
9.28
A
v
≈ −g
m1
g
m2
r
o1
r
o2
(Eq. 9.69)
= −
¸
2
_
W
L
_
1
µ
n
C
ox
I
D
¸
2
_
W
L
_
2
µ
n
C
ox
I
D
_
1
λI
D
_
2
= −2µ
n
C
ox
I
D
¸
_
W
L
_
1
_
W
L
_
2
_
1
λI
D
_
2
= −2µ
n
C
ox
1
I
D
1
λ
2
¸
_
W
L
_
1
_
W
L
_
2

A
v

I
D
9.30 From Problem 28, we have
A
v
= −2µ
n
C
ox
1
I
D
1
λ
2
¸
_
W
L
_
1
_
W
L
_
2
If we increase the transistor widths by a factor of N, we will get a new voltage gain A
′
v
:
A
′
v
= −2µ
n
C
ox
1
I
D
1
λ
2
¸
N
2
_
W
L
_
1
_
W
L
_
2
= −2Nµ
n
C
ox
1
I
D
1
λ
2
¸
_
W
L
_
1
_
W
L
_
2
= NA
v
Thus, the gain increases by a factor of N.
9.31 From Problem 28, we have
A
v
= −2µ
n
C
ox
1
I
D
1
λ
2
¸
_
W
L
_
1
_
W
L
_
2
If we decrease the transistor widths by a factor of N, we will get a new voltage gain A
′
v
:
A
′
v
= −2µ
n
C
ox
1
I
D
1
λ
2
¸
1
N
2
_
W
L
_
1
_
W
L
_
2
= −2
1
N
µ
n
C
ox
1
I
D
1
λ
2
¸
_
W
L
_
1
_
W
L
_
2
=
1
N
A
v
Thus, the gain decreases by a factor of N.
9.32
G
m
= −g
m2
R
out
= r
o2
[r
o3
+ (1 +g
m3
r
o3
) r
o4
]
A
v
= g
m2
{r
o2
[r
o3
+ (1 +g
m3
r
o3
) r
o4
]}
9.33
A
v
= −g
m1
{[r
o2
+ (1 +g
m2
r
o3
) r
o1
] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]}
= −500
g
m1
= g
m2
=
¸
2
_
W
L
_
µ
n
C
ox
I
D
g
m3
= g
m4
=
¸
2
_
W
L
_
µ
p
C
ox
I
D
r
o1
= r
o1
=
1
λ
n
I
D
r
o3
= r
o4
=
1
λ
p
I
D
I
D
= 1.15 mA
9.34 (a)
G
m
= g
m1
R
out
= [(r
o2
R
P
) + (1 +g
m2
(r
o2
R
P
)) r
o1
] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]
A
v
= −g
m1
{[(r
o2
R
P
) + (1 +g
m2
(r
o2
R
P
)) r
o1
] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]}
(b)
G
m
= g
m1
r
o1
R
P
1
gm2
+r
o1
R
P
R
out
= [r
o2
+ (1 +g
m2
r
o2
) (r
o1
R
P
)] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]
A
v
= −g
m1
r
o1
R
P
1
gm2
+r
o1
R
P
{[r
o2
+ (1 +g
m2
r
o2
) (r
o1
R
P
)] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]}
(c)
G
m
= g
m5
R
out
= [r
o2
+ (1 +g
m2
r
o2
) (r
o1
r
o5
)] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]
A
v
= −g
m5
{[r
o2
+ (1 +g
m2
r
o2
) (r
o1
r
o5
)] [r
o3
+ (1 +g
m3
r
o3
) r
o4
]}
(d)
G
m
= g
m5
R
out
= [r
o2
+ (1 +g
m2
r
o2
) r
o1
] [r
o3
+ (1 +g
m3
r
o3
) (r
o4
r
o5
)]
A
v
= −g
m5
{[r
o2
+ (1 +g
m2
r
o2
) r
o1
] [r
o3
+ (1 +g
m3
r
o3
) (r
o4
r
o5
)]}
9.36
I
1
=
1
2
µ
n
C
ox
W
L
_
R
2
R
1
+R
2
V
DD
−V
TH
_
2
(Eq. 9.85)
∂I
1
∂V
DD
=
W
L
µ
n
C
ox
_
R
2
R
1
+R
2
V
DD
−V
TH
_
R
2
R
1
+R
2
=
R
2
R
1
+R
2
g
m
Intuitively, we know that g
m
is the derivative of I
1
with respect to V
GS
, or g
m
=
∂I1
∂VGS
. Since V
GS
is
linearly dependent on V
DD
by the relationship established by the voltage divider (meaning
∂VGS
∂VDD
is a
constant), we’d expect
∂I1
∂VDD
to also be proportional to g
m
, since
∂I1
∂VDD
=
∂VGS
∂VDD
·
∂I1
∂VGS
=
∂VGS
∂VDD
g
m
.
9.37
I
1
=
1
2
µ
n
C
ox
W
L
_
R
2
R
1
+R
2
V
DD
−V
TH
_
2
(Eq. 9.85)
∂I
1
∂V
TH
= −µ
n
C
ox
W
L
_
R
2
R
1
+R
2
V
DD
−V
TH
_
The sensitivity of I
1
to V
TH
becomes a more serious issue at low supply voltages because as V
DD
becomes smaller with respect to V
TH
, V
TH
has more control over the sensitivity. When V
DD
is large
enough, it dominates the last term of the expression, reducing the control of V
TH
over the sensitivity.
9.38 As long as V
REF
> 0, the circuit operates in negative feedback, so that V
+
= V
−
= 0 V.
I
C1
= I
S1
e
−V1/VT
=
V
REF
R
1
V
1
= −V
T
ln
_
V
REF
R
1
I
S1
_
= V
BE2
If V
REF
> R
1
I
S1
, then we have V
BE2
< 0, and I
X
= 0. If V
REF
< R
1
I
S1
, then we have:
I
X
= I
S2
e
−VT ln
“
V
REF
R
1
I
S1
”
/VT
= I
S2
e
−ln
“
V
REF
R
1
I
S1
”
= I
S2
R
1
I
S1
V
REF
Thus, if V
REF
> R
1
I
S1
(which will typically be true, since I
S1
is typically very small), then we get no
output, i.e., I
X
= 0. When V
REF
< R
1
I
S1
, we get an inverse relationship between I
X
and V
REF
.
9.39 As long as V
REF
> 0, the circuit operates in negative feedback, so that V
+
= V
−
= 0 V.
I
C1
= I
S1
e
−V1/VT
=
V
REF
R
1
V
1
= −V
T
ln
_
V
REF
R
1
I
S1
_
= −V
BE2
If V
REF
< R
1
I
S1
, then we have V
BE2
< 0, and I
X
= 0. If V
REF
> R
1
I
S1
, then we have:
I
X
= I
S2
e
VT ln
“
V
REF
R
1
I
S1
”
/VT
= I
S2
V
REF
R
1
I
S1
=
I
S2
I
S1
V
REF
R
1
=
I
S2
I
S1
I
C1
Thus, if V
REF
< R
1
I
S1
, then we get no output, i.e., I
X
= 0. When V
REF
> R
1
I
S1
(which will typically
be true, since I
S1
is typically very small), we get a current mirror relationship between Q
1
and Q
2
(with I
X
copying I
C1
), where the reference current for Q
1
is
VREF
R1
(ensured by the opamp).
9.46 (a)
I
copy
= 5I
C,REF
I
REF
= I
C,REF
+I
B,REF
+I
B1
= I
C,REF
+
I
C,REF
β
+
I
copy
β
= I
C,REF
+
I
C,REF
β
+
5I
C,REF
β
= I
C,REF
_
1 +
1
β
+
5
β
_
=
I
copy
5
_
6 + β
β
_
I
copy
=
_
β
6 +β
_
5I
REF
(b)
I
copy
=
I
C,REF
5
I
REF
= I
C,REF
+I
B,REF
+I
B1
= I
C,REF
+
I
C,REF
β
+
I
copy
β
= I
C,REF
+
I
C,REF
β
+
I
C,REF
5β
= I
C,REF
_
1 +
1
β
+
1
5β
_
= 5I
copy
_
6 + 5β
5β
_
I
copy
=
_
5β
6 + 5β
_
I
REF
5
(c)
I
copy
=
3
2
I
C,REF
I
2
=
5
2
I
C,REF
I
REF
= I
C,REF
+ I
B,REF
+I
B1
+I
B2
= I
C,REF
+
I
C,REF
β
+
I
copy
β
+
I
2
β
= I
C,REF
+
I
C,REF
β
+
3I
C,REF
2β
+
5I
C,REF
2β
= I
C,REF
_
1 +
1
β
+
3
2β
+
5
2β
_
=
2
3
I
copy
_
10 + 2β
2β
_
I
copy
=
_
2β
10 + 2β
_
3
2
I
REF
9.49
V
GS,REF
= V
TH
+
¸
2I
REF
µ
n
C
ox
W
L
V
GS1
= V
GS,REF
−I
1
R
P
= V
TH
+
¸
2I
REF
µ
n
C
ox
W
L
− I
1
R
P
= V
TH
+
¸
2I
REF
µ
n
C
ox
W
L
−
I
REF
2
R
P
I
1
=
1
2
µ
n
C
ox
W
L
_¸
2I
REF
µ
n
C
ox
W
L
−
I
REF
2
R
P
_
2
=
I
REF
2
¸
2I
REF
µ
n
C
ox
W
L
−
I
REF
2
R
P
=
¸
I
REF
µ
n
C
ox
W
L
I
REF
2
R
P
=
¸
2I
REF
µ
n
C
ox
W
L
−
¸
I
REF
µ
n
C
ox
W
L
=
_
√
2 −1
_
¸
I
REF
µ
n
C
ox
W
L
R
P
=
2
_√
2 −1
_
_
I
REF
µ
n
C
ox
W
L
Given this choice of R
P
, I
1
does not change if the threshold voltages of the transistors change by the
same amount ∆V . Looking at the expression for I
1
in the derivation above, we can see that it has no
dependence on V
TH
(note that R
P
does not depend on V
TH
either).
9.54
I
C1
= 1 mA
I
E1
R
E
=
1 +β
n
β
n
I
C1
R
E
= 0.5 V
R
E
== 0.5 V
R
E
= 495.05 Ω
R
out,a
= r
o1
+ (1 +g
m1
r
o1
) (r
π1
R
E
)
= 85.49 kΩ
R
out,b
= r
o1
+ (1 +g
m1
r
o1
) (r
π1
r
o2
)
= 334.53 kΩ
The output impedance of the circuit in Fig. 9.72(b) is signiﬁcantly larger than the output impedance
of the circuit in Fig. 9.72(a) (by a factor of about 4).
9.56 (a)
R
out
= r
o1
+ (1 +g
m1
r
o1
) r
o2
= 200 kΩ
r
o1
= r
o2
=
1
λI
D
g
m1
= g
m2
=
_
2
W
L
µ
n
C
ox
I
D
_
W
L
_
1
=
_
W
L
_
2
= 1.6
(b)
V
b2
= V
GS2
= V
TH
+
¸
2I
D
W
L
µ
n
C
ox
= 2.9 V
9.57 (a) Assume I
C1
≈ I
C2
, since β ≫1.
A
v
= −g
m1
[r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)]
g
m1
= g
m2
=
I
1
V
T
r
o1
= r
o2
=
V
A
I
1
r
π1
= r
π2
= β
V
T
I
1
A
v
= −
I
1
V
T
_
V
A
I
1
+
_
1 +
V
A
V
T
_
β
VT
I1
VA
I1
β
VT
I1
+
VA
I1
_
= −
1
V
T
_
V
A
+
_
1 +
V
A
V
T
_
βV
T
V
A
βV
T
+V
A
_
= −500
V
A
= 0.618 V
(b)
V
in
= V
BE1
= V
T
ln
_
I
1
I
S1
_
= 714 mV
(c)
V
b1
= V
BE2
+V
CE1
= V
BE2
+ 500 mV
= V
T
ln
_
I
1
I
S2
_
+ 500 mV
= 1.214 V
9.58 Assume all of the collector currents are the same, since β ≫1.
P = I
C
V
CC
= 2 mW
I
C
= 0.8 mA
V
in
= V
T
ln
_
I
C
I
S
_
= 726 mV
V
b1
= V
BE2
+V
CE1
= V
T
ln
_
I
C
I
S
_
+V
BE1
−V
BC1
= 1.252 V
V
b3
= V
CC
−V
T
ln
_
I
C
I
S
_
= 1.774 V
V
b2
= V
CC
−V
EC4
−V
EB3
= V
CC
−(V
EB4
−V
CB4
) −V
T
ln
_
I
C
I
S
_
= 1.248 V
A
v
= −g
m1
{[r
o2
+ (1 +g
m2
r
o2
) (r
π2
r
o1
)] [r
o3
+ (1 +g
m3
r
o3
) (r
π3
r
o4
)]}
= 4887
9.62
R
out
= R
C
= 500 Ω
A
v
= g
m2
R
C
=
I
C
R
C
V
T
= 20
I
C
= 1.04 mA
P = (I
C
+I
REF
) V
CC
= 3 mW
I
REF
= 0.16 mA
I
C
=
A
E1
A
E,REF
I
REF
A
E1
A
E,REF
= 6.5
A
E,REF
= A
E
A
E1
= 6.5A
E
9.63
I
copy
= nI
C,REF
I
REF
= I
C,REF
+I
B,REF
+I
B1
= I
C,REF
+
I
C,REF
β
+
I
copy
β
= I
C,REF
+
I
C,REF
β
+
nI
C,REF
β
= I
C,REF
_
1 +
1
β
+
n
β
_
=
I
copy
n
_
n + 1 +β
β
_
I
copy
=
_
β
n + 1 +β
_
nI
REF
Since nI
REF
is the nominal value of I
copy
, the error term,
β
n+1+β
, must be between 0.99 and 1.01 so
that the actual value of I
copy
is within 1 % of the nominal value. Since the upper constraint (that the
error term must be less than 1.01) results in a negative value of n (meaning that we can only get less
than the nominal current if we include the error term), we only care about the lower error bound.
β
n + 1 +β
≥ 0.99
n ≤ 0.0101
I
REF
≥ 50 mA
We can see that in order to decrease the error term, we must use a smaller value for n (in the ideal
case, we have n approaching zero and the error term approaching
β
1+β
). However, the smaller value of
n we use, the larger value we must use for I
REF
, meaning the more power we must consume. Thus,
we have a direct tradeoﬀ between accuracy and power consumption.
9.64
I
C,M
=
A
E,M
A
E,REF1
I
C,REF1
I
REF1
= I
C,REF1
+I
B,REF1
+I
B,M
= I
C,REF1
+
I
C,REF1
β
n
+
I
C,M
β
n
= I
C,REF1
+
I
C,REF1
β
n
+
A
E,M
I
C,REF1
A
E,REF1
β
n
= I
C,REF1
_
1 +
1
β
n
+
A
E,M
A
E,REF1
β
n
_
=
A
E,REF1
A
E,M
I
C,M
_
A
E,REF1
β
n
+A
E,REF1
+A
E,M
A
E,REF1
β
n
_
I
C,M
=
_
A
E,REF1
β
n
A
E,REF1
β
n
+A
E,REF1
+A
E,M
_
A
E,M
A
E,REF1
I
REF
Using a similar derivation to ﬁnd I
C2
, we have:
I
C1
= I
C2
=
_
A
E,REF2
β
p
A
E,REF2
β
p
+A
E,REF2
+A
E2
_
A
E2
A
E,REF2
I
C,M
=
_
A
E,REF1
β
p
A
E,REF1
β
p
+A
E,REF1
+A
E,M
__
A
E,REF2
β
p
A
E,REF2
β
p
+A
E,REF2
+A
E2
_
A
E,M
A
E,REF1
·
A
E2
A
E,REF2
I
REF
We want the error term to be between 0.90 and 1.10 so that I
C2
is within 10 % of its nominal value.
Since the error term cannot exceed 1 (since we only lose current through the base), we only have to
worry about the lower bound.
_
A
E,REF1
β
n
A
E,REF1
β
n
+A
E,REF1
+ A
E,M
__
A
E,REF2
β
p
A
E,REF2
β
p
+A
E,REF2
+A
E2
_
≥ 0.90
Let’s let the reference transistors Q
REF1
and Q
REF2
have unit size A
E
. Then we have:
_
β
n
β
n
+ 1 +
AE,M
AE
__
β
p
β
p
+ 1 +
AE2
AE
_
> 0.90
We can pick any A
E,M
and A
E2
such that this constraint is satisﬁed. One valid solution is A
E,M
= A
E
,
A
E2
= 3.466A
E
, and I
REF
= 0.2885 mA. This gives a nominal value for I
C2
of 1 mA with an error
of 10 %. This solution is not unique (for example, another solution would be A
E,M
= A
E2
= A
E
and
I
REF
= 1 mA, which gives a nominal current of 1 mA and an error of 5.73 %).
9.68
A
v
= g
m1
r
o3
= g
m1
1
λ
p
I
D1
= 20
R
in
=
1
g
m1
r
o2
=
r
o2
1 +g
m1
r
o2
=
1
λnID1
1 +g
m1
1
λnID1
= 50 Ω
g
m1
= 19.5 mS
I
D1
= 4.88 mA
g
m1
=
¸
2µ
n
C
ox
_
W
L
_
1
I
D1
_
W
L
_
1
= 390
We need to size the rest of the transistors to ensure they provide the correct bias current to the ampliﬁer
and to ensure they are all in saturation. V
G3
will be important in determining how we should bias
V
G5
, since in order for M
5
to be in saturation, we require V
G3
> V
G5
−V
THn
, and V
G3
is ﬁxed by the
previously calculated value of I
D1
.
V
G3
= V
DD
−V
SG3
= V
DD
−
_
V
THp
 +
¸
2I
D1
µ
p
C
ox
_
W
L
_
3
_
= 0.363 V
Let’s let I
REF
= I
D5
= 1 mA (which ensures we meet our power constraint, since P = (I
REF
+I
D5
+I
D1
) V
DD
=
12.4 mW) and V
GS,REF
= V
GS5
= 0.5 V (which ensures M
5
operates in saturation). Then we have
I
REF
=
1
2
µ
n
C
ox
_
W
L
_
REF
(V
GS,REF
− V
TH
)
2
_
W
L
_
REF
=
_
W
L
_
5
=
360
0.18
(W/L)
3
(W/L)
4
=
I
D3
I
D4
_
W
L
_
4
=
8.2
0.18
(W/L)
2
(W/L)
REF
=
I
D2
I
REF
_
W
L
_
2
=
1756
0.18
This action might not be possible to undo. Are you sure you want to continue?
We've moved you to where you read on your other device.
Get the full title to continue reading from where you left off, or restart the preview.